(untitled) (American Journal of Pedagogical and Educational Research, 2023)
It aimed was to identify the level of gifted students’ possession of innovative thinking. The researcher used the descriptive analytical approach to suit the variables of the study, and the study community consisted of students of all gifted schools in Iraq, which are (7) schools, and the study sample was chosen in a deliberate way to reach the number of members of the study community (320) students for the academic year 2022/2021, and the researcher prepared the study tool, which is the questionnaire, and it was distributed to the members of the study sample consisting of (34) students .